2021
DOI: 10.3390/ijerph18115675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Muscle Strength, Aerobic Capacity and Body Composition between Healthy Adolescents and Those Living with HIV: A Systematic Review and Meta-Analysis

Abstract: Background: The adverse effects of antiretroviral therapy associated with complications generated by human immunodeficiency virus (HIV) promote impairments in physical fitness in adolescents. Objective: To analyze the aerobic capacity, muscle strength, and body composition of adolescents living with HIV compared with a healthy population of the same age. Methods: Searches were performed in the MEDLINE, Embase, Web of Science, Scopus and SportDiscus databases until September 2019 and updated in April 2020. Elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, the results from these scoping reviews show the lack of knowledge in terms of understanding the importance of the physical activity level as a moderating factor in the relationship between HIV infection/ART use and the health-related physical fitness components in HIV-diagnosed children and adolescents in terms of the physical activity level investigation [48,49,53]. Another limitation of the interpretation of these studies is the difference between HIVdiagnosed children and adolescents when compared whit their peers without a diagnosis of HIV infection [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results from these scoping reviews show the lack of knowledge in terms of understanding the importance of the physical activity level as a moderating factor in the relationship between HIV infection/ART use and the health-related physical fitness components in HIV-diagnosed children and adolescents in terms of the physical activity level investigation [48,49,53]. Another limitation of the interpretation of these studies is the difference between HIVdiagnosed children and adolescents when compared whit their peers without a diagnosis of HIV infection [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary search was conducted in January 2024, through the search tools of the Medical Literature Analysis and Retrieval System Online (MEDLINE) (via PubMed), Cochrane Library, Joana Briggs Institute (JBI) Evidence Synthesis and Open Science Framework (OSF) to identify scoping reviews or systematic reviews that mapped the healthrelated physical fitness of HIV-diagnosed children and adolescents. Two systematic reviews with meta-analysis were found, which aimed to investigate muscle function and aerobic capacity in HIV-diagnosed patients [54], and to investigate the aerobic capacity, muscle strength and body composition of HIV-diagnosed adolescents [55]. However, those reviews included only studies that compared results of HIV-diagnosed participants with…”
Section: Preliminary Searchmentioning
confidence: 99%
“…It is known that nutritional counseling and exercise interventions in adults with HIV are effective in treating obesity, fat redistribution, and metabolic abnormalities, however, in the pediatric population, investigations need to be further examined [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Evidence suggests that an approach of anticipation and accountability for nutrition and concern with the level of physical activity can improve the results and help minimize the adverse consequences (metabolic, cardiovascular, and psychological) of HIV [ 1 , 38 , 39 ], mainly during the development and maturation phases [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those reported are often small, lack a control population [10,11], or focus on treatment-naive individuals [12]. A recent systematic review of just five cross-sectional studies (none in Africa), totalling 197 adolescents (age 16-18 years) living with HIV, identified reduced muscle strength and physical fitness compared with uninfected peers [13]. In adults, findings are mixed, for example, raltegravir-based therapy has been associated with skeletal muscle toxicity [14], whilst tenofovir alafenamide (TAF) has been associated with greater muscle mass in men [15].…”
Section: Introductionmentioning
confidence: 99%